1977
DOI: 10.2172/7290879
|View full text |Cite
|
Sign up to set email alerts
|

Cleanup of radioactive mud spill U20aa postshot drilling site NTS

Abstract: PRIOR TO CLEANUP PROCEDURES 4. MUD SUMP-FOLLOWING CLEANUP PRXEMTRES 5. DECONTAMINATION EQUIPMENT IN AREA 2 , 6. FOLLLIWING INITIAL MUD EU3FlOVA.L IN AREA 3 7. VACUUM CLEANING SYSTE_hl 8. PRIOR TO CLEANUP IN AREA 4 9. DURING CLEANUP IN AREA 4-SHOVELING & SAGGING 0. .DURING CLEANUP IN AREA 5-SHaVELING .& BAGGING .11. FOLLLIWIhG CLEANUP IN AREA 5 12. EARTHEN DAM & END OF CONTAPilINATED MUD FIX)id

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2.1. 7 Area 20 Straume et al (1977Straume et al ( , 1978 report on the cleanup of a large area of rugged terrain following a spill of radioactively contaminated mud. Precleanup surveys indicated that 103 Ru and 106 Ru/Rh were the primary nuclides present, with total estimated activity at the time of release of 38 and 6 Ci (1.41 X 10 12 and 2.22 X 10 11 Bq), respectively.…”
Section: Area 13mentioning
confidence: 99%
“…2.1. 7 Area 20 Straume et al (1977Straume et al ( , 1978 report on the cleanup of a large area of rugged terrain following a spill of radioactively contaminated mud. Precleanup surveys indicated that 103 Ru and 106 Ru/Rh were the primary nuclides present, with total estimated activity at the time of release of 38 and 6 Ci (1.41 X 10 12 and 2.22 X 10 11 Bq), respectively.…”
Section: Area 13mentioning
confidence: 99%